The impact of repeated NALC/NaOH- decontamination on the performance of Xpert MTB/RIF assay. (May 2018) - Rachow, Andrea; Saathoff, Elmar; Mtafya, Bariki; Mapamba, Daniel; Mangu, Chacha; Rojas-Ponce, Gabriel; Ntinginya, Nyanda E.; Boeree, Martin; Heinrich, Norbert; Gillespie, Stephen H.; Hoelscher, Michael; ,
Abstract: The Xpert MTB/RIF assay detects Mycobacterium tuberculosis in unprocessed or NALC/NaOH- decontaminated sputum. The effect of repeated NALC/NaOH-decontamination on several Xpert performance parameters was assessed in this study. A second NALC/NaOH-decontamination had no effect on the binary Xpert-outcome but increased the value for the quantitative readout ( C Tmin ). Repeated decontamination was not associated with PCR-inhibition or invalid results. The C Tmin of M.tb positive samples was higher in inhibited Xpert runs. Our data indicate that NALC/NaOH-decontamination has an effect on the performance of the Xpert assay, and that C Tmin readouts of decontaminated sputum samples should be interpreted with caution.